Physical activity and sedentary behaviour in European children: the IDEFICS study. Issue 10 (8th October 2013) - Santaliestra-Pasías, Alba Ma; Mouratidou, Theodora; Verbestel, Vera; Bammann, Karin; Molnar, Dénes; Sieri, Sabina; Siani, Alfonso; Veidebaum, Toomas; Mårild, Staffan; Lissner, Lauren; Hadjigeorgiou, Charalambos; Reisch, Lucia; et al.
Abstract Objective To estimate the prevalence of physical activity and sedentary behaviours in European children, and to evaluate the relationship between media availability in personal space and physical activity in relation to total screen time. Design Data from the baseline IDEFICS (Identification and prevention of dietary- and lifestyle-induced health effects in children and infants) cross-sectional survey. Information on hours of television/digital video disk/video viewing and computer/games-console use (weekday and weekend days), media device availability in personal space, sports club membership, hours of active organized play and commuting (to and from school) were assessed via a self-reported parental questionnaire. Total screen time was defined as the sum of daily media use and subsequently dichotomized into meeting or not meeting the guidelines of the American Academy of Pediatrics. Setting Eight survey centres (Italy, Estonia, Cyprus, Belgium, Sweden, Germany, Hungary and Spain). Subjects Children (n 15 330; 51 % males) aged 2–10 years. Results Percentage of children engaged in total screen time for >2 h/d was higher on weekend days (52 % v. 20 % on weekdays) and in the older group (71 % in males; 57 % in females), varying by country. Children with a television set in their bedroom were more likely not to meet the screen time recommendations (OR = 1·54; 95 % CI 1·60, 1·74). Conclusions Approximately a third of the children failed to meet current screen time recommendations. Availability of a television set in personal space increased the risk of excess total screen time. This information could be used to identify potential targets for public health promotion actions of young population groups.